Profil dan Rasionalitas Penggunaan Obat Antihipertensi di Puskesmas Jawa Tengah - Asmaurini Pramudya; Rachmad Bagas Yahya Supriyono; Kristiyani Asuk; Jusman Jusman; Richa Yuswantina (SEHATI: Jurnal Kesehatan, 2026)
Hypertension is a major public health problem and a leading cause of cardiovascular morbidity and mortality. Rational use of antihypertensive drugs is essential to achieve optimal blood pressure control, particularly in primary healthcare settings. This study aimed to evaluate the profile and rationality of antihypertensive drug use at Pringapus and Cebongan Primary Health Centers, Central Java, during June–August 2025. An observational analytic study with a retrospective design was conducted using medical record data of hypertensive patients. The evaluation included patient characteristics, patterns of antihypertensive prescribing, and the rationality of drug use based on appropriate indication, drug selection, and dosage. Rationality was assessed according to the 2024 Guidelines for Hypertension Management in Primary Healthcare and the Drug Information Handbook 23rd edition. The results showed that most patients were elderly and female, with stage 1 hypertension being the most common diagnosis. Calcium channel blockers, particularly amlodipine, were the most frequently prescribed antihypertensive drugs. Overall, antihypertensive drug use demonstrated good rationality; however, several cases of inappropriate drug selection and dosage were identified. In conclusion, antihypertensive therapy at the studied primary healthcare centers was generally consistent with current guidelines, although continuous evaluation is required to optimize prescribing practices